2018
DOI: 10.1093/ije/dyy114
|View full text |Cite
|
Sign up to set email alerts
|

Errors in estimating usual sodium intake by the Kawasaki formula alter its relationship with mortality: implications for public health†

Abstract: Background: Several cohort studies with inaccurate estimates of sodium reported a J-shaped relationship with mortality. We compared various estimated sodium intakes with that measured by the gold-standard method of multiple non-consecutive 24-h urine collections and assessed their relationship with mortality. Methods: We analysed the Trials of Hypertension Prevention follow-up data. Sodium intake was assessed in four ways: (i) average measured (gold standard): mean of three to seven 24-h urinary sodium measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
82
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 41 publications
5
82
0
Order By: Relevance
“…When Olde Engberink et al assessed multiple 24‐hour urine collections over 1‐5 years, there were substantially different estimates of individual sodium intake, and the risk of cardiovascular disease increased progressively with intake. Similarly, in the Trials of Hypertension Prevention (TOHP), estimates of sodium intake from an average of multiple 24‐hour urine collections had a statistically significant linear relationship with death, while the association was relatively flat, and not statistically significant when sodium intake, was measured by a single 24‐hour urine collection . Further, in the TOHP studies, when the Kawasaki equation was used to estimate 24‐hour urine sodium from the sodium concentration in 24‐hour urine collections, the association with death was not statistically significant and appeared to take on a J‐shaped curve.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…When Olde Engberink et al assessed multiple 24‐hour urine collections over 1‐5 years, there were substantially different estimates of individual sodium intake, and the risk of cardiovascular disease increased progressively with intake. Similarly, in the Trials of Hypertension Prevention (TOHP), estimates of sodium intake from an average of multiple 24‐hour urine collections had a statistically significant linear relationship with death, while the association was relatively flat, and not statistically significant when sodium intake, was measured by a single 24‐hour urine collection . Further, in the TOHP studies, when the Kawasaki equation was used to estimate 24‐hour urine sodium from the sodium concentration in 24‐hour urine collections, the association with death was not statistically significant and appeared to take on a J‐shaped curve.…”
Section: Discussionmentioning
confidence: 99%
“…Weaver et al found that ten 24‐hour urine collections were required to have a 75% reliability to estimate an individual's sodium intake when on a constant sodium diet and this number is likely higher when there is substantial day‐to‐day variation in sodium intake. The strength of the association between dietary sodium and health outcomes is highly influenced by the number of urine collections . The issues relating to current, short‐term, and long‐term estimates of sodium intake for populations also apply to individuals.…”
Section: ‐Hour Urine Collections To Assess Healthy Individual's Sodmentioning
confidence: 99%
See 2 more Smart Citations
“…This study, despite having been judged by the Panel to be at low risk of bias (tier 1), has important limitations. There is strong evidence for a linear dose-response relationship of salt with blood pressure (He 2002(He , 2003, and also with cardiovascular events (Cook, 2014) and mortality (He, 2018), within the range of 3 to 12 grams of salt per day. In addition, we have concern over the possibility of undercollection of 24h urine samples in this study, which could have led two problematic findings, i.e.…”
Section: Risk Of Cardiovascular Diseasesmentioning
confidence: 99%